Gender equality: Women's empowerment for rural revitalization - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Malapit, Hazel J. (International Food Policy Research Institute, 2019)
Rural revitalization requires that all members of society, including women, be able to participate in and benefit from growth and transformation of rural areas. Achieving gender equality is a key step toward achieving many of the Sustainable Development Goals and can enhance women’s contribution to rural revitalization. Women’s empowerment can improve agricultural productivity, dietary quality, and maternal and child nutrition. These connections are especially evident in rural areas. This chapter describes how use of a “reach-benefit-empower” framework can guide the development of programs and policies that will increase gender equity and women’s empowerment for better rural lives.